PENGEMBANGAN DECISION SUPPORT SYSTEM UNTUK MENUNJANG LAYANAN IT JARINGAN DATA DI BPPT - Haikal Andrean (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The development of technology and information is currently growing quite rapidly. And every organization of a company is required to utilize technology and information to become a plus for the company or organization. Currently BPPT uses the osTicket and iTop applications to support daily operations for BPPT's business needs.The purpose of this research is to build a system that can provide information for IT managers in making decisions in the network infrastructure. The methodology used in this case is the study of literature and observe directly condition in BPPT. The data used are derived from two applications at BPPT (osTicket and itop) where the data must be able to interact and integrate with each other. Results of the research is to be achieved there is a comprehensive so that can be used in decision making by IT managers.Conclusions obtained is a system of decision-making in the operational of the IT network due to problems that occur repeatedly can be minimized or eliminated by given solution on information obtained from the decision support system.